UMP hosts MASUM Sports Tournament Phase 1 - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 24 March 2022 - After two years of MASUM Sports Tournament being suspended, the MASUM Phase 1 sports carnival was held face-to-face involving the Ministry of Higher Education (MOHE) and Universiti Malaysia Pahang (UMP) as the host.